Emission taxes and the design of refunding schemes - Gersbach, Hans; Requate, Tilman (CESifo working papers, 2000)
We examine how emission taxes should be refunded to firms in order to create optimal incentives to invest in cleaner technologies. Since refunds cannot be made dependent on investments, an alternative way is to give back taxes to firms according to market shares. We show that universally applicable refunding schemes must be linear in market shares. Moreover, a socially optimal tax/tax refunding scheme exists if pollution is proportional to output and firms compete à la Cournot. If short-term abatement technologies exist, tax/tax refunding schemes can still provide second-best allocations. If firms are price takers, however, refunding taxes according to market shares is harmful. Since imperfect competition is a prominent phenomenon in many polluting industries, the design of socially optimal refunding schemes is an essential part of environmental regulation.
Keywords: Graue Literatur; Dyopol; Optimale Besteuerung; Investition; Umweltschutz; Umweltsteuer